Epigenetic perturbation driving asleep telomerase reverse transcriptase: Possible therapeutic avenues in carcinoma - Ajay Kumar; Pritish Nilednu; Azad Kumar; Nilesh Kumar Sharma (Tumor Biology)
In the last decade, implications of human telomerase reverse transcriptase (hTERT), a component of ribonucleoprotein telomerase in aging, senescence, and stem cell are highly evident. Besides, the activation of hTERT is also being documented several cancer types including carcinoma. The awakening of telomerase during carcinoma initiation and development is being seen with different perspectives including genetic and epigenetic tools and events. In view of several tumor progenitors genes (also referred as epigenetic mediators), telomerase is placed as key enzyme to achieve the carcinoma phenotype and sustain during the progression. It is true that swaying of telomerase in carcinoma could be facilitated with dedicated set of epigenetic modulators and modifiers players. These epigenetic alterations are heritable, potentially reversible, and seen as the epigenetic signature of carcinoma. Several papers converge to suggest that DNA methylation, histone modification, and small non-coding RNAs are the widely appreciated epigenetic changes towards hTERT modulation. In this review, we summarize the contribution of epigenetic factors in the telomerase activation and discuss potential avenues to achieve therapeutic intervention in carcinoma.